HUBUNGAN ANTARA KECERDASAN SOSIAL DENGAN KEAKTIFAN BELAJAR SISWA DI MI MUHAMMADIYAH 2 SINGKAWANG - Suwanda; Dina Anika Marhayani; Kariadi, Dodik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problem in this study is based on the learning process where students do not give a good response, this can be seen when the teacher explains that they do not get enough attention, when given questions only a few can answer, besides that students are also found to be less confident in expressing their opinions. This study aims to determine whether or not there is a relationship between social intelligence and student learning activity at MI.Muhammadiyah 2 Singkawang. The research method used is correlation research with a quantitative approach. The objects of this study were students in grades IV, V and VI at MI.Muhammadiyah 2 Singkawang totaling 64 students. Data collection used a student social intelligence questionnaire and a student learning activity questionnaire. Data were analyzed using descriptive statistics, the analysis requirements test used the normality test with the Kolmogorov-Smirnov test and the linearity test used the Deviation From Linearity. Hypothesis testing used the Pearson Product Moment correlation test. The results of the analysis show that there is a significant relationship between social intelligence and student learning activity at MI.Muhammadiyah 2 Singkawang which is indicated by a correlation value of 0.50 which means it has sufficient criteria based on the level of correlation and has a positive correlation direction.